A Holistic Look at Minimizing Adverse Environmental Impact Under Section 316(b) of the Clean Water Act. (2002) - Veil, John A.; Puder, Markus G.; Littleton, Debra J.; Johnson, Nancy
Abstract : Section 316(b) of the Clean Water Act (CWA) requires that "the location, design, construction, and capacity of cooling water intake structures reflect the best technology available for minimizing adverse environmental impact." As the U.S. Environmental Protection Agency (EPA) develops new regulations to implement Section 316(b), much of the debate has centered on adverse impingement and entrainment impacts of cooling-water intake structures. Depending on the specific location and intake layout, once-through cooling systems withdrawing many millions of gallons of water per day can, to a varying degree, harm fish and other aquatic organisms in the water bodies from which the cooling water is withdrawn. Therefore, opponents of once-through cooling systems have encouraged the EPA to require wet or dry cooling tower systems as the best technology available (BTA), without considering site-specific conditions. However, within the context of the broader scope of the CWA mandate, this focus seems too narrow. Therefore, this article examines the phrase "minimizing adverse environmental impact" in a holistic light. Emphasis is placed on the analysis of the terms "environmental" and "minimizing." Congress chose "environmental" in lieu of other more narrowly focused terms like "impingement and entrainment, " "water quality, " or "aquatic life." In this light, BTA for cooling-water intake structures must minimize the entire suite of environmental impacts, as opposed to just those associated with impingement and entrainment. Wet and dry cooling tower systems work well to minimize entrainment and impingement, but they introduce other equally important impacts because they impose an energy penalty on the power output of the generating unit. The energy penalty results from a reduction in plant operating efficiency and an increase in internal power consumption. As a consequence of the energy penalty, power companies must generate additional electricity to achieve the same net output. This added production leads to additional environmental impacts associated with extraction and processing of the fuel, air emissions from burning the fuel, and additional evaporation of freshwater supplies during the cooling process. Wet towers also require the use of toxic biocides that are subsequently discharged or disposed. The other term under consideration, "minimizing, " does not equal "eliminating." Technologies may be available to minimize but not totally eliminate adverse environmental impacts.